Empowerment Of Rural Community Based On The Agroindustry Of Local Food - Siti Syamsiar; Vini Arumsari (Jurnal Dinamika Sosial Ekonomi, 2010)
The Agroindustry of local food in rural areas in an activity that can improve indigenous resources. All of local potencies done in rural area, not only to get benefit, but also to increase the role of agroindustry. The development of agroindustry is able to increase local food added value, income and opportunities for employment, and so far to get higher regional economic growth. One of the agroindustry in Kokap District, Kulon Progo is "Sumber Rejeki", a group of farmers that produce granulated coconut palm sugar. This group is the pioneer on producing granulated coconut palm sugar. The objective of this paper are to identify indigenous resources based on granulated coconut palm sugar industry; to analyze the role of agroindustry in improving farmers income and job opportunities, and to elaborate the role of farmers group as the centre of institutional improvement. Survey method was used to collect data with qualitative and quantitative data in the area. The result show that "Sumber Rejeki" farmers group has empowered the rural community by increasing the added value, income and employment opportunities through agroindustry of granulated coconut palm sugar.Key words: Agroindustry, Added Value, Income, Opportunities for Employment, Farmer Group